PROFESSOR H. F. ADAMS AND THE TWO-FACTOR THEORY OF ABILITY. - Thouless, Robert H. (Journal of Applied Psychology)
The article comments on the paper "An Objectivity-subjectivity Ratio for Scales of Measurement," by H. F. Adams in a 1930 issue of "The Journal of Social Psychology." It is argued that whether or not Adams' approach of differentiating between subjective and objective scales will be found to be useful and valid, his results have no effect whatsoever on the theory of general ability.